Dual-combination maintenance inhaler preferences in asthma and chronic obstructive pulmonary disease: A patient-centered benefit-risk assessment. (January 2021) - Tervonen, Tommi; Martinez, Fernando J.; Hanania, Nicola A.; Heidenreich, Sebastian; Eudicone, James M.; Gilbert, Ileen
Abstract: Background: A variety of dual-combination maintenance inhalers are used to treat asthma and chronic obstructive pulmonary disease (COPD). Understanding patient preferences for treatment attributes may help select an optimal treatment from the patient perspective. Methods: Patient preferences for maintenance inhaler device and medication attributes were elicited through a discrete choice experiment and used in benefit-risk assessments to calculate predicted choice probabilities (PrCPs) for 14 dual-combination maintenance inhalers in four treatment classes: lower- and higher-dose inhaled corticosteroid (ICS)/long-acting beta agonist (LABA) inhalers for asthma, and ICS/LABA and long-acting muscarinic antagonist (LAMA)/LABA inhalers for COPD. Results: For all treatment classes, reduced exacerbations and faster onset of action were the most important attributes. For all classes, patients were willing to tolerate an extra yearly exacerbation to decrease the medication's onset of action from 30 to 5 min. For patients with asthma using lower-dose ICS/LABA (n = 497), budesonide/formoterol fumarate dihydrate (80 μg/4.5 μg) pressurized metered-dose inhaler (pMDI) had the highest PrCP (28.4%), and for those using a higher-dose ICS/LABA (n = 285), PrCPs were highest for mometasone furoate/formoterol fumarate dihydrate (200 μg/5 μg) pMDI (27.0%) and budesonide/formoterol fumarate dihydrate (160 μg/4.5 μg) pMDI (26.9%). For patients with COPD using an ICS/LABA (n = 574), budesonide/formoterol fumarate dihydrate (160 μg/4.5 μg) pMDI had the highest PrCP (56.6%), and for those using a LAMA/LABA inhaler (n = 217), tiotropium/olodaterol (2.5 μg/2.5 μg) soft mist inhaler had the highest PrCP (42.3%). Conclusions: Patient preference data for maintenance inhaler attributes can be used to identify a preference order of inhalers in different treatment classes. Highlights: Patient preference data for maintenance inhaler attributes can be used to identify a preference order of inhalers. Patients using inhalers of different treatment classes differed only in their preferences for device type and dose counter. Differences between predicted preference and actual prescriptions highlight importance of considering the patient perspective.